Integrated analysis of microbiome and transcriptome reveals the mechanisms underlying the chlorogenic acid-mediated attenuation of oxidative stress and systemic inflammatory responses via gut-liver axis in post-peaking laying hens - Zhaoying Hu; Lianchi Wu; Yujie Lv; Chaoyue Ge; Xinyu Luo; Shenao Zhan; Weichen Huang; Xinyu Shen; Dongyou Yu; Bing Liu (Journal of Animal Science and Biotechnology)
Abstract Background Systemic inflammatory responses and oxidative stress occur in laying hens during the aging process, particularly during the post-peaking laying period, which generally result in multi-organ damages, leading to significant declines in egg performance and quality. Chlorogenic acid (CGA)-enriched extract from Eucommia ulmoides leaves has anti-inflammatory and antioxidant activities. However, the mechanisms underlying whether and how CGA alleviates systemic inflammatory responses and oxidative stress to improve egg performance and quality in post-peaking laying hens remain unclear. In this study, the potential regulatory mechanisms of CGA in alleviating inflammatory responses and oxidative stress along the gut-liver axis were investigated. A total of 360 55-week-old Hy-line white-laying hens were randomly selected and divided into four groups. The hens in the four groups were fed a basal diet (CON) or basal diets supplemented with 200, 400, and 800 mg/kg of CGA (CGA200, CGA400, and CGA800, respectively) for 10 weeks. Results The results demonstrated that CGA significantly alleviated intestinal and hepatic damages resulting from systemic inflammatory responses and oxidative stress, thereby improving the laying performance and egg quality of post-peaking laying hens. CGA reduced systemic inflammation by improving intestinal barrier function and modulating inflammation-associated microbiota (Blautia and Megamonas), thus inhibiting endotoxin translocation. CGA can also reduce oxidative stress by upregulating the NRF-2 pathway-related genes and increasing antioxidant enzyme activities in the liver. The results of transcriptome sequencing revealed that CGA promoted lipid metabolism by regulating hepatic adipocytokine pathway-related genes/protein and reduced the inflammatory responses and apoptosis in liver by regulating PI3K/AKT pathway-related genes/proteins, which was also verified by qPCR and western blotting. Conclusion CGA alleviated multi-organ damages and dysfunction by suppressing the systemic inflammatory responses and oxidative stress in post-peaking laying hens, thereby improving egg performance and quality. The optimal dose of CGA is 400 mg/kg in this experiment. These results provide a sound theoretical basis for the application of CGA as an exogenous animal feed additive for laying hens.